2018
DOI: 10.3390/en12010127
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Heat Extraction Performance of Fractured Geothermal Reservoir Using Coupled Thermal-Hydraulic-Mechanical Model Based on Equivalent Continuum Method

Abstract: Natural fractures and artificial fractures in a tight rock matrix of an enhanced geothermal system make flow and heat transfer become seriously anisotropic. In this paper, a field-scale fractured heterogeneous geothermal reservoir model is built to study the heat transfer process. Based on an equivalent continuum method and local thermal non-equilibrium model, an equivalent permeability tensor is mapped from discrete fractures and a coupled thermal-hydraulic-mechanical mathematical model is adopted in which lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The authors showed that higher heat extraction could be achieved in CO 2 ‐based EGS than water‐based EGS for more substantial formation permeability. The continuum model used by Wang et al assumed fracture properties embedded in the matrix; this fails to mimic a fractured reservoir accurately. Guo et al conducted a performance evaluation of EGS using CO 2 as a working fluid under THM coupling technique.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that higher heat extraction could be achieved in CO 2 ‐based EGS than water‐based EGS for more substantial formation permeability. The continuum model used by Wang et al assumed fracture properties embedded in the matrix; this fails to mimic a fractured reservoir accurately. Guo et al conducted a performance evaluation of EGS using CO 2 as a working fluid under THM coupling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2014) evaluated the production performance of the Songliao Basin through the coupling of reservoir and wellbore, and found that ideal thermal efficiency and total output power could be obtained at the initial stage of operation, but the total output power dropped significantly after 30 years of operation. Wang et al (2019) established a THM coupling mathematical model, studied the flow, stress and temperature of HDR reservoir under different injection flow rates based on the equivalent continuum method, and studied the heat extraction performance of EGS, but there were too few influence factors in the study. Zhou et al (2022) established a THM coupling model for injection and production of HDR and compared the heat extraction performance of water injection development of HDR without considering coupling, partial coupling and full coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Including fractures in numerical thermohydromechanical (THM) models is possible and several approaches have been proposed (e.g., Keilegavlen et al., 2021; Pan et al., 2014; T. Wang et al., 2019; Yao et al., 2018; Zareidarmiyan, Salarirad, et al., 2020). Yet, explicitly accounting for fractures in numerical models of poromechanical problems is a challenging task and often comes at the expenses of a very high computational cost (Lei et al., 2017; McDermott & Kolditz, 2006; Pandey et al., 2017; Salimzadeh et al., 2018; Thomas et al., 2020; Yoshioka et al., 2019).…”
Section: Introductionmentioning
confidence: 99%